Near-infrared fluorescent pyrrolopyrrole cyanine derivatives and colloidal nanoparticles with tunable optical properties for in vivo bioimaging - Huang, Shuo (2020)
Near infrared (NIR) fluorescent molecules with light absorption and emission above 700 nm are important for noninvasive and deep-tissue imaging for disease diagnosis and imaging-guided surgery. Nevertheless, currently available NIR fluorophores with high fluorescence quantum yields and robust photostability remain rather limited. Here we report a series of π-extended pyrrolopyrrole cyanine (PPCy) derivatives with tunable light absorption and emission in the NIR spectral region. The extent of the intramolecular charge transfer shows significant effect on the optical bandgap, the Stokes shift and the fluorescence quantum yield. These hydrophobic PPCy derivatives were dispersed as colloidal nanoparticles into water via a nanoprecipitation process. The nanoparticles composed of spirofluorene-flanked PPCy derivatives exhibit the optimal optical properties, effective tumor-targeting, and high fluorescence contrast for in vivo bioimaging of xenografted tumor-model mice.